PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 173593 PARSOBURAN KAB. TOBA - Lubis, Nela Chintya Permatasari; Patri Janson Silaban; Antonius Remigius Abi; Darinda Sofia Tanjung; Heka Maya Sari Br Sembiring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to determine the effect of the Think Pair Share cooperative learning model on the mathematics learning outcomes of fourth- grade students of SD Negeri 173593 Parsoburan. The research method used is an experimental method which is classified as a quantitative reseach type. The sample of this study was all IV grade students totaling 28 students, so the sampling technique used saturated samples. The results of data analysis showed that the average pre-test score of 60,14 increased to 84,14 in the post-test. The results of this study indicate that the mathematics learning outcomes of fourth-grade students of SD Negeri 173593 Parsoburan are included in the veru strong category with a correlation coefficient of 0,959 so that rcount (0,959) ≥ rtable (0,374). The results of hypothesis testing show that tcount (17,244) ≥ ttable (2,056), so Ha is accepted and Ho is rejected. The results of this study indicate that there is a significant positive influence between the cooperative learning model of the Think Pair Share type on the mathematics learning outcomes of fourth-grade students of SD Negeri 173593 Parsoburan. This is proven by the coefficient of 0,919, which means that 91,9% of the model used is effective in improving the learning outcomes of fourth-grade students of SD Negeri 173593 Parsoburan.